In situ and ex situ studies of microstructure evolution during high-temperature oxidation of ZrN hard coating. (1st March 2015) - Qi, Z.B.; Wu, Z.T.; Liang, H.F.; Zhang, D.F.; Wang, J.H.; Wang, Z.C.
Abstract : Microstructure evolution during oxidation of ZrN coating at 650 °C was investigated by in situ and ex situ methods. The results reveal the simultaneous occurrence of epitaxially growing tetragonal ZrO2 near the ZrO2 –ZrN interface and transformation from preformed tetragonal to monoclinic phase close to the oxide surface. The significant volume expansion associated with tetragonal → monoclinic transformation plays a major role in producing interconnected microcracks and pores across the oxide scale, which provide fast diffusion paths of oxygen and hence lower the oxidation resistance of ZrN coating.